Simulium maleewongae, a New Species of Simulium (Gomphostilbia) (Diptera: Simuliidae) From Thailand - Takaoka H. (2017)
© The Authors 2016. Published by Oxford University Press on behalf of Entomological Society of America. All rights reserved. For Permissions, please email: journals.permissions@oup.com Version of Record, first published online October 20, 2016 with fixed content and layout in compliance with Art. 8.1.3.2 ICZN. Simulium (Gomphostilbia) maleewongae sp. nov. is described based on the adult males and females, their pupal exuviae, and larvae from Thailand. This new species is placed in the Simulium gombakense species-group of Simulium (Gomphostilbia). It is characterized by the female cibarium with a cup-like appendage, male ventral plate deeply depressed ventromedially, pupal gill composed of an inflated structure and eight slender filaments, cone-shaped pupal terminal hooks, and cocoon with an anterodorsal projection. Taxonomic notes are given to separate this new species from 10 other species of the same species-group known from China, India, Malaysia, Thailand, Nepal, and Vietnam. Keys to identify all 11 species of the S. gombakense species-group are provided for females, males, pupae, and larvae.